Composição florística de uma área de campo úmido no município de Analândia, São Paulo - Sousa, Naiara Lopes de [UNESP] (2014)
(Floristic composition of an area of moist grassland in Fazenda Pedra Vermelha, Analândia, São Paulo). The moist grassland phyto-physiognomy integrates the Cerrado biome near springs and streams, and in areas with shallow groundwater. This vegetation presents a very typical flora, due the particular soil conditions that restrict and select the species. Among the layers that compose the Cerrado, the herbaceous-subshrub is the least contemplated in terms of floristic evaluation, because the presence of many species in wetlands may still be unknown. The main objective of this study was to record the species of vascular plants in moist grassland in Fazenda Pedra Vermelha, at Analândia municipality, São Paulo state, and to compare the floristic composition with others wetlands areas in this state. The area has 5ha and is located at coordinates 22º07'50”-08'01”S and 47º46'40’-53”O, and at altitudes ranging from 760 to 770 meters. The floristic survey was carried along 18 months. The floristic similarity was calculated using the Jaccard Index. A total of 178 species, 121 genera and 62 families of vascular plants were registered in the area. Asteraceae (19 species), Cyperaceae (15), Poaceae (14) Melastomaceae (13) Xyridaceae and Eriocaulaceae (8) were the most rich families. A new species for Cyperaceae was diagnosed and 7 species endangered were found. The floristic similarity between the wet grassland sampled and the four areas compared was low. The results show a significant floristic richness of the wet grassland at the Fazenda Pedra Vermelha